The molecular mechanisms of alkylating agent-related acute myeloid leukaemia (Hematology Meeting Reports, 2009)
Alkylating chemotherapy agents are used with considerable success to treat numerous human malignancies, including lung cancer, breast cancer, Hodgkin lymphoma and multiple myeloma. Alkylating agents encompass a broad range of structurally diverse agents that includes nitrogen mustards, methylating agents, platinating agents and nitrosoureas.